2020
DOI: 10.1111/ppl.13275
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the new dimensions of selenium research to understand the underlying mechanism of its uptake, translocation, and accumulation

Abstract: Selenium (Se) is a vital mineral for both plants and animals. It is widely distributed on the earth's crust and is taken up by the plants as selenite or selenate. Plants substantially vary in their physiological response to Se. The amount of Se in edible plants is genetically controlled. Its availability can be determined by measuring its phytoavailability in soil. The low concentration of Se in plants can help them in combating stress, whereas higher concentrations can be detrimental to plant health and in mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 142 publications
0
18
0
1
Order By: Relevance
“…In addition to passive uptake, active uptake of Se (selenite and selenate) is conditioned by mechanisms that are similar to those responsible for sulphur and phosphorus transportation. Thus, the form in which the plant absorbs Se is also partially impacted by differences in phosphate and sulphate concentrations in soil and plants [ 59 ]. In alkaline conditions, like those found at the investigated sites, selenate dominates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to passive uptake, active uptake of Se (selenite and selenate) is conditioned by mechanisms that are similar to those responsible for sulphur and phosphorus transportation. Thus, the form in which the plant absorbs Se is also partially impacted by differences in phosphate and sulphate concentrations in soil and plants [ 59 ]. In alkaline conditions, like those found at the investigated sites, selenate dominates.…”
Section: Discussionmentioning
confidence: 99%
“…A reduction in pH favours the dominance of selenite, the uptake of which is an active process mediated by phosphate transporters [ 60 ]. The lower pH of FA at L2, as well as the deficit of bioavailable P in FA at L1, and especially at L2, resulted in increased phosphate transporter activity in tamarisk, which may cause a significant increase in selenite uptake [ 59 ]. In contrast, it was found that an increase in phosphate concentrations in soil decreased Se uptake rates by 20–70% in the herbaceous plants Lolium perenne , Trifolium fragiferrum , Astragalus canadensis , A. bisulcatus and Triticum aestivum [ 61 , 62 , 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…Transgenic plants have been engineered with greater Se tolerance, Se accumulation or reduced Se volatilization than their non-transgenic counterparts [197]. An example of this is the SeCys methyltransferase gene of Astragalus bisulcatus (two-grooved poison vetch) which was introduced into Arabidopsis thaliana to overexpress Se-methyl SeCys and g-glutamyl methyl SeCys in plant shoots [198], which resulted in an increased accumulation of Se within the plant. Other genes have been successfully targeted by genetic engineering in the last decade, with positive outcomes for Se bio-fortification.…”
Section: Biofortification Of Selenium Through Genetic Engineering Andmentioning
confidence: 99%
“…Se absorption, transport, and translocation are influenced by a variety of parameters, including the quantity and type of Se in the environment, plant species, medium pH, and the presence of Sulphur and phosphorus ( Rasool et al., 2022 ). Agricultural soils are predominantly richer in selenate than selenite and the selenate being more water soluble is readily absorbed as compared to selenite ( Raina et al., 2021 ). As a result of the chemical analogy of selanate/selenite with sulphate and phosphate, their behavior in metabolism and transport in plants is closely related ( Raina et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Agricultural soils are predominantly richer in selenate than selenite and the selenate being more water soluble is readily absorbed as compared to selenite ( Raina et al., 2021 ). As a result of the chemical analogy of selanate/selenite with sulphate and phosphate, their behavior in metabolism and transport in plants is closely related ( Raina et al., 2021 ). A high concentration of Se seems to promote the pathway of “Starch and sucrose metabolism” as its treatment resulted in the accumulation of both forms of carbohydrates in potato ( Solanum tuberosum L.) ( Turakainen et al., 2004 ).…”
Section: Introductionmentioning
confidence: 99%